Luminescence of the elpasolite series M I2M IIMCl 6 (M I=Cs, Rb; M II=Li, Na; M = Lu, Y, Sc, In) doped with europium using synchrotron radiation excitation - Tanner, P.; Duan, C.; Jia, Guohua; Cheng, B. (Elsevier, 2012)
The excitation and emission spectra of a series of cubic hexachloroelpasolites doped with europium have been investigated using synchrotron radiation at 10 K. Besides the Eu3 emission from 5D J (J=0-3) multiplets, emission from 5H 3 is also observed for Cs 2Naln 0.995Eu 0.005Cl6, since the gap to the next lowest level is spanned by seven phonons. The excitation spectra of samples indicate impurities due to oxygen and divalent europium. Broad band emission from Eu 2+ is reported from the crystalline samples grown in vacuum by the Bridgman process, with the maximum wavelength shifting to the red with increasing lattice parameter for the series Cs 2NaMCl 6:Eu 2+ (M=Lu, Y, Eu). © 2012 Elsevier Inc. All rights reserved.